Profil Kemampuan Pemecahan Masalah Peserta Praktik Kerja Lapangan SMK Negeri Kota Surabaya - Handayani, Riska Willyanti; Habsy, Bakhrudin Al; Christiana, Elisabeth; Naqiyah, Najlatun; Mursanyoto, Heru (Universitas Nusantara PGRI Kediri, 2023)
To support the progress of vocational education in the 21st century, this study aims to analyze students' problem-solving abilities during fieldwork practice. The method used was a survey involving 362 students in classes XII and XIII of public vocational schools in Surabaya. This study uses an instrument that adopts the perspective of the six-thinking hat. The instrument consists of 20 statement items with answer options in the form of a linear scale and 1 item of answer options in the form of checkboxes. The results showed that the percentage of students' problem-solving ability was in the very high category of 6,4%, the high category of 28,5%, the medium category of 45,6%, the low category of 15,7%, and the very low category of 3,9%. This study also revealed that of the 8 skills required during the PKL, the